PENGARUH MODEL TATA KELOLA BAGI PEDAGANG KAKI LIMA DALAM MENJALANKAN USAHANYA DI KOTA SOLO - Edhi Wasisto (Universitas Slamet Riyadi, 2019)
The objective of this research is to identify factors influencing the management and arrangement of street vendors around Pasar Klewer Solo and explain the impact of PKL structuring on business performance through a quantitative research model. The methods of data collection in this study are: observation guides, interviews, questionnaires, and documentation. Data analysis is divided into two stages namely descriptive and infrensial statistics. The infrared statistics use Partial Least Square (PLS). The sample was chosen purposively, amounting to 10% of the population. The results obtained in this study are: (1) The street vendors around Klewer Market in Solo City have various characteristics. When viewed from the characteristics of sex street vendors who operate in the area around the campus is dominated by men that is equal to 79,27%, when viewed from the business field characteristics of 61,36% food sales business, when viewed from the characteristic age of 54,05 % is in the productive age of 25-30 years, when viewed from education of 48,65% high school education and when viewed from the number of employees of 50.45% have 3-7 employees; (2) The management of human resources and operational management have an influence to the business performance of street vendors around Pasar Klewer in Solo proven with the result of calculation PLS where both variables have t value bigger than t table (HR Management 3,276, Operational management 2,679 > 1,96); (3) The management of finance and marketing does not have an effect on the business performance of street vendors in Klewer Market in Solo City because at the time of modification of the initial model both have less than 0.50 loading factor for each indicator; (4) Performance of PKL business area around Klewer Market in Solo City is influenced by human resource management which is reflected by labor and operational management which is reflected by workflow. The direction of the influence of HR management variables is negative, if the PKL wants to improve their performance then the labor they use should come from outside the family. While the operational management variables in the form of performance should be able to be improved by street vendors to improve their performance.Keywords: Model of PKL governance in Solo City.